2008
DOI: 10.1002/ajp.20608
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation, consolation and postconflict behavioral specificity in chimpanzees

Abstract: Conflicts of interest arise regularly in the lives of all group-living animals and may escalate into aggressive conflicts. The costs of aggressive escalation can be reduced through peaceful postconflict interactions. This study investigated the postconflict behavior of 22 adult chimpanzees at Chester Zoo. The occurrence of reconciliation, i.e. the postconflict affiliative reunion between conflict opponents, and consolation, i.e. a postconflict affiliative interaction directed from a third party to the recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 50 publications
5
62
1
3
Order By: Relevance
“…This fission -fusion dynamic means that individual group members are not always in visual contact, creating a scenario where robust cognitive mechanisms for representing individual identity would be highly advantageous. This is additionally supported by many behaviours shown by chimpanzees that require recognition and long-term memory for specific individuals, including reconciliation and consolation, and specific patterns of reciprocity and cooperation [84,85]. Recent data suggest that the flexibility inherent in a fission-fusion society may be associated with the coevolution of unique cognitive strategies, including response inhibition that would enable individuals to respond flexibly to a changing social dynamic [86].…”
Section: Resultsmentioning
confidence: 94%
“…This fission -fusion dynamic means that individual group members are not always in visual contact, creating a scenario where robust cognitive mechanisms for representing individual identity would be highly advantageous. This is additionally supported by many behaviours shown by chimpanzees that require recognition and long-term memory for specific individuals, including reconciliation and consolation, and specific patterns of reciprocity and cooperation [84,85]. Recent data suggest that the flexibility inherent in a fission-fusion society may be associated with the coevolution of unique cognitive strategies, including response inhibition that would enable individuals to respond flexibly to a changing social dynamic [86].…”
Section: Resultsmentioning
confidence: 94%
“…Affiliative behavior after conflicts tends to occur between victims of conflict and other conspecifics (consolation) or between opponents (reconciliation). This bonding behavior can strengthen the social bonds between participants (Clay & de Waal, 2015; Cordoni & Palagi, 2008; De Waal & Vanroosmalen, 1979; Fraser & Bugnyar, 2011; Seed, Clayton, & Emery, 2007; Wittig & Boesch, 2010), protect from further aggression (Call, Aureli, & De Waal, 2002; Koski & Sterck, 2009; Palagi, Chiarugi, & Cordoni, 2008), and reduce baseline GCs or behavioral signs of stress in the victim (Castles & Whiten, 1998; Duboscq, Agil, Engelhardt, & Thierry, 2014; Fraser & Aureli, 2008; Fraser, Stahl, & Aureli, 2008; McFarland & Majolo, 2012). …”
Section: Evidence That Variation In Stress Physiology Is Associated Wmentioning
confidence: 99%
“…7,10 The majority of research on post-conflict behavior has focused on reconciliation, the affiliative post-conflict interaction between former opponents, 11,12 but important post-conflict interactions may also occur between the opponents and bystanders uninvolved in the previous conflict. 13,14 In particular, a number of recent studies have demonstrated the phenomenon of post-conflict affiliation directed from a bystander to the recipient of aggression in a variety of species from primates [15][16][17][18][19][20][21][22][23][24][25] to dogs 26 and rooks. 27 This review focuses on bystander to recipient interactions and examines the variations in their patterns, which are consistent with a number of different functional explanations.…”
Section: Introductionmentioning
confidence: 99%
“…29 Such a differentiation has been further supported by the fact that a number of studies have found evidence for the occurrence of post-conflict bystander affiliation solicited by the recipient of aggression but not for similar affiliation offered by the bystander, [29][30][31] or for the occurrence of unsolicited affiliation but not affiliation solicited by the recipient of aggression. 16,17,19,20 The role of the conflict participant may also be important in discriminating between different post-conflict interactions involving bystanders. 13,14 Whereas de Waal and van Roosmalen 28 focused on recipients of aggression only, many later studies did not differentiate between recipients of aggression and aggressors.…”
Section: Introductionmentioning
confidence: 99%